Effect of Low Temperatures on the Mechanical Performance of GFRC Modified by Low Carbon Cement - Meimei Song; Chuanlin Wang (Advances in Civil Engineering)
Glass fibre reinforced cement (GFRC) is a composite material with great ductility but it undergoes severe strength and ductility degradation with ageing. Calcium sulfoaluminate (CSA) cement is low carbon cement, and more importantly, it exhibits great potential to produce more ductile and durable GFRC. This study focuses on mechanical performance, e.g., compressive strength, stress-strain curve, and freeze-thaw resistance of CSA/GFRC as well as its microstructural characteristics under low temperatures. XRD was applied to investigate the hydration mechanism of CSA cement under −5°C, 0°C, and 5°C. It was found out that low-temperature environments have very little effect on the type of hydration products, and the main hydration product of hydrated CSA cement cured under low temperatures is ettringite. Moreover, low-curing temperatures have an adverse effect on the compressive strength developments of CSA/GFRC but the strength difference compared with that under 20°C reduces gradually with increasing curing ages. In terms of bending performance, both ultimate tensile strength and ultimate strain value indicate considerable degradation with ageing under low temperatures after 14 d. The ultimate strain value reduces to 0.34% at −5°C, 0.39% at 0°C, and 0.44% at 5°C compared with 0.51% for that cured at 20°C for 28 d. The tensile strength of samples cured at −5°C for 28 d is only 15.2 MPa, taking up only 40% of that under 20°C. CSA/GFRC also demonstrated great capability in the antifreeze-thaw performance, and the corresponding strength remains 95.9%, 94.7%, 94.2%, and 94.3%, respectively, for that cured under 20°C, 5°C, 0°C, and −5°C after 50 freeze-thaw cycles. Microstructural studies reveal that densification of the interfilamentary space with intermixtures of C-A-S-H and ettringite is the main reason that causes the degradation of CSA/GFRC, which may result in loss on flexibility when forces are applied, therefore reducing the post-peak toughness to some extent.